Construction cluster innovation - Payne, David; Sarvaranta, Leena (International Journal of Strategic Property Management, 2010)
“Construction cluster innovation”International Journal of Strategic Property Management, 9(2), p. 53-54.First Published Online: 18 Oct 2010